Aplikasi Pakan Konsentrat Berbasis Bahan Lokal Untuk Meningkatken Kualitas Karkas Sapi (Sapi Pesisir) - Khasrad Khasrad (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2007)
The present research was studied the effect of feeding level od fattening period on the carcass characteristics (percentage of carcass, back fat thickness and loin eye area) of Pesisir cattle. Treatments of feeding included: Al = 50 % concentrate + 50 % ammoniated rice straw, A2 = 75 % concentrate + 25 % ammoniated rice straw. The feed were offered in two fattening periods of B1 = 3 months and B2 = 4 months. Data were statistically analized in randomized block design with three blocks. Results showed that there was no interaction effect between the levels of feeding and fattening periods to the percentage of carcass, the back fat thickness and the loin eye area of the Pesisir cattle (P> 0,05). The higher of concentrate percentage used in the feed and the longer the fattening period were followed by the thicker the back fat and the wider the loin eye area (P<0.05).